Correlation between clinical, radiological and arthroscopic findings in cases of osteoarthritis of knee joint - Kuila, Pritam Kalyan; Hazra, Rishov; Ahmed, Arshad; Roy, Rajiv (International Journal of Research in Medical Sciences, 2024)
Background: Osteoarthritis (OA) is the most common degenerative joint disorder and a major public health problem throughout the world. The knees are the most commonly affected joints. In view of multiple conflicting reports in the literature the present study was undertaken to study the correlation amongst radiological, arthroscopic and pain findings in knee OA patients to facilitate early and precise diagnosis leading to appropriate and timely treatment. Methods: Total 53 (39 female and 14 male) cases of primary OA were screened and selected for our study. Apley’s pain score equated to Visual Analogue Score and Western Ontario and MacMaster Universities Osteoarthritis score (WOMAC) sub scales were used for assessment of pain, stiffness and physical function respectively. Radiographic evaluation were done according to Kellgren-Lawrence Grading scale (X-ray) and modification of Outerbridge classification system (MRI). Outerbridge classification system was used to assess arthroscopic findings. Results: Clinical symptom of pain had statistically significant correlation with stiffness, physical disability, radiological severity and arthroscopic findings. Stiffness and physical disability scores individually doesn’t have any statistically significant correlation with MRI and arthroscopic severity. Radiological findings were found to corroborate with the arthroscopic findings significantly. Conclusions: Radiological and clinical findings in combination should be considered in concluding the final diagnosis and treatment of OA knee. Improvised criteria for precise diagnosis yet to be evolved.